Comparative Analysis of the Science Teaching Curricula in Turkey - Yaz, Ömer Volkan; Kurnaz, Mehmet Altan (SAGE Publications, 2020)
The purpose of this study is to comparatively investigate the science teaching curricula in Turkey, which have undergone changes four times since the millennium. For this purpose, we carried out a technical and taxonomic examination of the learning outcomes listed in the science curricula that were introduced in 2000, 2005, 2013, and 2017 concerning Revised Bloom Taxonomy (RBT). In this study, the document analysis method was used. We classified a total of 2,613 learning outcomes in our analyses, which were limited to those related to the cognitive domain. The reliability score of the classifications was .89 according to the equation proposed by Miles and Huberman. The analyses showed that the teaching curricula decreased the intensity of the focus on knowledge and cognitive skills rather than making fundamental changes. Moreover, there was significant parallelism among the examined curricula in terms of the dimensions of the taxonomy. Using national-level results in international exams such as PISA (Programme for International Student Assessment) and TIMSS (Trends in International Mathematics and Science Study), we concluded that Turkey had not been successful enough in developing the examined curricula.
Keywords: H; AZ20-999; Social Sciences; History of scholarship and learning. The humanities; 4. Education; 10. No inequality